OP54 Measuring the impact of a public awareness campaign to increase Welfare Power of Attorney registrations in Scotland. (13th September 2016) - Levin, KA; Carson, J; Cummings, A; Jarvie, H; Crighton, E
Abstract : Background: Welfare power of attorney (WPOA) is a legal document in which one individual gives authority to another to act or make welfare and health care decisions for them, in the event that they become incapacitated. Thus, having a WPOA safeguards individuals' treatment preferences and wishes. Having a WPOA in place can also prevent delays in discharge from hospital, therefore reducing length of stay and unnecessary associated costs. A recent study found a lack of awareness of the need for WPOA among the general public. A public awareness campaign, 'My Power of Attorney', was implemented in Glasgow City and subsequently other parts of Scotland in 2013–2015. Methods: WPOA registration data were analysed between January 2010 and June 2015. Multilevel Poisson models for WPOA registrations nested by council and annual quarter were run using MCMC methods, adjusting for time, campaign (variable ranging between 0–5 dependent on intensity of campaign measured by the number of media platforms received), and offset term mid-year population estimate for those aged 25 years+/65 year+. Results: WPOA registrations saw a reduction between 2010 and 2011 but overall, increased between 2010 and 2015. WPOA registrations rose by 33.3% in Glasgow City between 2013 and 2014, when the campaign began, while for the rest of Scotland saw a rise of 17.3%. When the data were modelled, the relative risk of a registration for those living in an area with the any of the campaign was significantly greater than those receiving no campaign. Relative risk increased with increasing intensity of campaign, so that the RR of a new registration in an area in receipt of the full campaign was RR = 1.31 (1.28, 1.34) that of an area with no campaign. There was an approximate dose-response relationship with intensity of campaign, although the full campaign, a score of 5, was associated with a far greater RR than a score of 4. The associations became more pronounced when the 65 year+, rather than 25 year+, population was used as an offset term. Between council variation persisted after adjustment for campaign (Variance = 0.059 (0.015)). A random slope for the time variable suggested variance between councils increased over time. Conclusion: During the period of the campaign, area-level increases in WPOA registrations were observed associated with the 'My Power of Attorney' timing and location, in an approximate dose-response relationship with campaign intensity, suggesting that this is likely to be due to the campaign that began in Glasgow City.